Prevalence and risk factors for Alzheimer's disease and related dementias in Ghana: evidence from a cross-sectional population-based study - Paul Okyere; Emmanuel Appiah-Brempong; Arti Singh; Suparna Qanungo; Peter Donkor; Charles Mock (Taylor & Francis Group, 2024)
Alzheimer's disease and Related Dementia (ADRD) is a growing concern for low- and middle-income countries. Yet, studies on the prevalence and risk factors for dementia in sub-Saharan Africa are limited. This study estimated the prevalence and identified the risk factors for ADRD in Ghana. A cross-sectional design involving 384 participants aged 60 years or more completed the Brief Community Screening Instrument for Dementia (CSID) with an additional set of questions on risk factors. The prevalence of dementia was 16% (62/384). Age (AOR = 1.031 (95% CI 1.002-1.061, p = 0.035), education (AOR = 0.689 (95% CI 0.517-0.919, p = 0.011), and employment (AOR = 0.320 (95% CI 0.149-0.685, p = 0.004) were associated with dementia. Also, 'experience of stressful life event from age 16-64' (AOR = 1.325 (95% CI 1.034-1.698, p = 0.024), 'experience of stressful life event from age 65+' (AOR = 1.258 (95% CI 1.024-1.546, p = 0.042), and 'activities of daily living' (AOR = 0.925 (95% CI 0.868-0.986, p = 0.037) identified as risk factors of dementia. The burden of ADRD was high. Urgent actions are needed to address this problem. There is a possibility that the burden of dementia may have been overestimated because of the study instrument. Findings should be interpreted in light of this limitation.